Clock synchronization in industrial Internet of Things and potential works in precision time protocol: Review, challenges and future directions - Balakrishnan K; Dhanalakshmi R; Bam Bahadur Sinha; Gopalakrishnan R (International Journal of Cognitive Computing in Engineering, 2023)
The Internet of Things (IoT) aims to revolutionize users' daily lives by enabling seamless data exchange among various ubiquitous devices over the Internet. However, achieving this broad objective can pose significant challenges for applications that require synchronized timing, such as ensuring the temporal sequencing of data or synchronized performance of activities. IoT networks typically comprise entities with varying resources, making it challenging to implement existing time synchronization methods like N.T.P. (Network Time Protocol) on resource-constrained devices. On the other hand, solutions that work for constrained systems may not be scalable across diverse IoT deployments. This survey paper delves into the clock synchronization issues in IoT installations where applications require a unified perception of time. The article describes clock synchronization solutions for various models and their associated performance and discusses several research challenges related to clock synchronization. Additionally, a review of time synchronization techniques is provided to aid IoT practitioners in selecting the most relevant aspects for deployment.